The concept of human microcosm: exploring possibilities of a synthesis of traditional and modern biomedicine - Bakar, Osman (Springer International Publishing, 2021)
The idea of human microcosm as understood in traditional Islamic civilisation is important to its natural theology, but it is also known to have found scientific applications in many branches of knowledge, including medicine. In the light of the traditional definition of human microcosm that depicts it as a hierarchical but integrated living system with constituent parts similar to those of the rest of the universe, this paper proposes to identify some of the most essential elements and features of this system, which together have gone to form the foundation of traditional “biomedicine.” The three most important constituent parts of the traditional human microcosm are the body, the soul (nafs), and the spirit (ruh). In traditional Islamic science attempts were made to harmonise between the theological and scientific approaches to the formulation and understanding of the interrelationships linking these three microcosmic entities. The two approaches were held to be complementary to each other. This paper will try to formulate the biological dimension of these microcosmic interrelationships and its implications for medicine as may be gathered from the traditional literature on the subject. The concept of human microcosm thus understood that was viewed as bearing a certain “relationship of correspondence” with its macrocosmic counterpart was found to have given a further insight into what the correspondence could mean for biomedical issues, especially when the correspondence was formulated at the biological level.